Comportamiento agronómico de un híbrido promisorio de maíz forrajero (Zea mays L.), durante la época lluviosa en las zonas ganaderas del Ecuador - Amat Cabrera, Génesis Elizabeth (2019)
Trials were established in four locations along the Ecuadorian coast, during the rainy season of 2019, with the objective of evaluating and identifying the agronomic behavior of a promising hybrid of QPM fodder corn, comparing it with other genetic materials that are also used as feed fodder. of ruminants, at two cutting times at 70 and 80 days after sowing, for this purpose the experimental scientific method was used under the design of completely random blocks with factorial arrangement A x B being A (genetic material) and B (days of cut), for each locality the experimental plots consisted of furrows of 5 m long, separated from each other at 0.40 m and 0.20 m between plants, the analysis of variance by locality was carried out in addition to the test of 5% Tukey to determine the ranges of significance. The analysis of variance did not determine statistical differences in the genetic material interaction or cut, but if among genetic material in some study variables, the promising hybrid of forage corn obtained higher averages in important variables such as the yields of fresh forage weight in t ha-1 and dry matter than the control materials. The location with the highest productivity in fresh fodder yields was in Pichilingue and Chone, being the promising hybrid of fodder corn that obtained the best results in averages with 117.81 t ha-1 at 80 days of cutting and 74.81 t ha-1 at 70 days of cutting, and dry matter with 22.00 t ha-1 and 18.44 t ha-1 respectively. Concluding that the promising hybrid of forage corn gives excellent results and it is advisable to sow it at this density and in these locations in the rainy season.